Enhancing financial reporting quality in village-owned enterprises: The role of organizational competencies - Sudarlan Sudarlan; Surahman; Nurita Affan; Putri Maghfirah Vidhiyanty; Lutfilatul Hasanah (Public and Municipal Finance)
The quality of financial reporting in village-owned enterprises (VOEs) is critical for ensuring transparency and accountability in local governance. This study explores the impact of education level, training programs, work experience, internal control systems, and information technology on the quality of financial reports in VOEs. The objective is to determine how these factors influence financial reporting quality to support effective local governance. The paper involves a sample of 120 VOE managers and employs quantitative analysis to examine the relationships between these factors and the quality of financial reporting in Indonesia. The results indicate that higher education levels, comprehensive training programs, and extensive work experience positively affect the quality of financial reporting. Specifically, the study finds that educated personnel and well-structured training programs enhance the accuracy and reliability of financial reporting. In contrast, the anticipated positive impact of IT utilization on financial reporting quality was not observed, suggesting that issues related to IT infrastructure and integration may limit its effectiveness. Additionally, robust internal control systems significantly improve the quality of financial reports. Overall, the analysis emphasizes the importance of investing in education, training, and internal controls to enhance financial reporting quality in VOEs. The findings highlight the need for further research into the challenges of IT integration to fully harness its benefits for financial transparency.